Contrast Gain Shapes Visual Time - Bruno, Aurelio; Johnston, Alan (Frontiers in Psychology, 2010)
Traditionally time perception has been considered the product of a central, generic, cognitive mechanism. However, evidence is emerging for a distributive system with modality-specific sensory components (Johnston et al. 2006; Morrone et al. 2005). Here we show that fast contrast adaptation, which can be observed in the retina, induces a change in apparent duration. The perceived duration of a sub-second interval containing a 50% luminance contrast drifting pattern is compressed when it follows a high (90%) as compared to a low (10%) contrast interval. The duration effect cannot be attributed to changes in latency at onset relative to offset, can be dissociated from the effect of contrast context on apparent speed or apparent contrast per se and it occurs in a retinocentric frame of reference. The temporal compression is limited to high drift temporal frequencies (≥10Hz) and is not observed for equiluminant chromatic stimuli. This pattern of results indicates a major role for the magnocellular pathway in the neural encoding and representation of visual time.